The Influence of Financial Literacy on Consumer Behavior (Case Study of Medan City Society) - Harefa, Hilda Syaf'aini (INDONESIAN JOURNAL OF SUSTAINABILITY, 2025)
This study aims to determine and analyze financial literacy influences consumer behavior in the Medan City community. This type of research is quantitative descriptive. The population in this study is the Medan City community. The sample in this study was 96 respondents. The data analysis methods used were Instrument Test, Classical Assumption Test, Simple Linear Regression Test, Hypothesis Test and Determination Coefficient Test (R2) using the SPSS Version 25 for Windows program. The results of the study showed that economic literacy had a positive and significant effect on consumer behavior in the Medan City community